THE IMPACT OF WIND ON THE UNIFORMITY OF PESTICIDE SPRAYING IN FIELD TREATMENT USING UNMANNED AERIAL VEHICLES - RODINKOV, YURII; SAVYTSKYI, ANTON (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper presents an in-depth mathematical modeling of the pesticide spraying process using unmanned aerial vehicles (UAVs), focusing on the impact of wind on the uniformity and efficiency of liquid distribution. The use of UAVs in agriculture has become widespread due to their capability for precise and targeted application of agrochemicals. However, environmental factors such as wind introduce significant challenges by altering droplet trajectories and causing non-uniform spraying and chemical drift. This study systematically analyzes the main operational and environmental parameters affecting spraying efficiency, including nozzle pressure, nozzle orifice diameter, the physical properties of the sprayed liquid (density, viscosity, surface tension), flight altitude, and the characteristics of ambient wind. Special emphasis is placed on the aerodynamic interactions between droplets and wind flows, which result in droplet displacement, changes in droplet velocity vectors, and distortion of the spray cone angle. A detailed mathematical model is proposed to predict these effects. The model is based on solving the system of differential equations describing droplet motion under the combined influence of gravitational and aerodynamic drag forces, with the wind velocity vector acting as a dynamic external perturbation. Analytical expressions are derived for estimating the deformation of the spray pattern and the effective treatment swath under varying wind conditions. The results provide a scientific basis for the development of adaptive UAV-based spraying systems that can dynamically adjust flight parameters (altitude, speed, nozzle settings) in response to real-time wind measurements. This approach offers significant potential for improving pesticide application efficiency, reducing environmental contamination, and supporting the sustainable intensification of agricultural practices within the framework of precision farming technologies.